2008
DOI: 10.1007/s10295-008-0342-9
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional xylanases and their potential use in biotechnology

Abstract: Plant cell walls are comprised of cellulose, hemicellulose and other polymers that are intertwined. This complex structure acts as a barrier to degradation by single enzyme. Thus, a cocktail consisting of bi and multifunctional xylanases and xylan debranching enzymes is most desired combination for the efficient utilization of these complex materials. Xylanases have prospective applications in the food, animal feed, and paper and pulp industries. Furthermore, in order to enhance feed nutrient digestibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 83 publications
(82 reference statements)
0
60
0
4
Order By: Relevance
“…After digestion, the DNA fragment was cloned into the Pichia expression pPICZaA vector at the SacII/XbaI sites and transformed into Escherichia coli DH5α, then confirmed for the correct expression frame by sequencing. The chimeric gene was constructed by end-to-end fusion (Khandeparker and Numan 2008). Firstly, the Lip gene was obtained via PCR amplification using the forward primer 7 with restriction enzyme sites of EcoRI (Underlined), and reverse primer 8.…”
Section: Construction Of Eg1cd Lip and Chimera Lip-eg1cdmentioning
confidence: 99%
See 1 more Smart Citation
“…After digestion, the DNA fragment was cloned into the Pichia expression pPICZaA vector at the SacII/XbaI sites and transformed into Escherichia coli DH5α, then confirmed for the correct expression frame by sequencing. The chimeric gene was constructed by end-to-end fusion (Khandeparker and Numan 2008). Firstly, the Lip gene was obtained via PCR amplification using the forward primer 7 with restriction enzyme sites of EcoRI (Underlined), and reverse primer 8.…”
Section: Construction Of Eg1cd Lip and Chimera Lip-eg1cdmentioning
confidence: 99%
“…Because endoglucanase and lipase have shown high deinking efficiency (Gübitz et al 1998;Morkbak et al 1999;Marques et al 2003;Pelach et al 2003;Vyas and Lachke 2003), the authors assumed that the combined use of two enzymes could promote better deinking efficiency. With such assumption, a chimeric enzyme with endoglucanase and lipase activities was constructed in this study by an end-to-end fusion technique, in which the Lip catalytic domain at N-terminus was fused with the EG1 catalytic domain at C-terminus (Khandeparker and Numan 2008). Several studies have suggested that linker peptides between the individual moieties may play an important role in maintaining the proper conformation and function of the moieties (Shan et al 1999;Lu and Feng 2008).…”
Section: Design Of the Chimera Lip-eg1cdmentioning
confidence: 99%
“…To take advantage of this feature, we designed chimeric enzymes based on XynCDBFV and AxeS20E. Chimeric enzymes are usually created by an end-to-end fusion technique, in which the N terminus of one catalytic domain is linked to the C terminus of the other catalytic domain (Khandeparker and Numan 2008). The sequential order of catalytic domains in chimeric enzymes may affect the enzyme specific activities Hong et al 2006).…”
Section: Design Of the Chimeric Xylanolytic Enzymesmentioning
confidence: 99%
“…Fusion protein techniques are commonly used for purifying recombinant proteins, monitoring protein expression, displaying proteins on the cell surface, biological screening, targeting proteins, and so on (Hong et al 2006). Fusion proteins are usually created by an end-to-end fusion technique, in which the N terminus of one domain is linked to the C terminus of the other domain (Khandeparker and Numan 2008). Several studies have indicated that selection of proper linkers with a certain degree of flexibility and hydrophilicity is very important (Shan et al 1999;Xue et al 2004;Lu and Feng 2008).…”
Section: Specific Activities Of the Parental And Chimeric Enzymes On mentioning
confidence: 99%
“…Other important applications of xylanases are to make the bread fine and soft and extend the storage time 3 ; to purify fruit juice, wine and beer 4 ; and to form xylitol glucose used in confectionery industry. In the breeding, xylanase expedites the digestion process of food containing xylan and at the same time helps to reduce the viscosity in the digestive system followed by many positive effects such as improved food absorption, improved microorganism populations of the intestine in the advantageous direction, reduced digestion disorder, and drier excrement 5,6 . Among filamentous fungi, Trichoderma and Aspergillus have been widely studied for the xylanase production, and the genus Aspergillus is the most efficient producers of xylanolytic enzymes [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%